Perceived physical health in obsessive-compulsive disorder: a protocol for a systematic review and meta-analysis. Issue 6 (7th June 2019) - Pozza, Andrea; Ferretti, Fabio; Coluccia, Anna
Abstract : Introduction: Obsessive-compulsive disorder (OCD) is a mental health condition associated with severe impairment in a variety of quality of life domains, an increased physical health burden, and a higher risk of general medical conditions and mortality compared with the general population. While there is a large amount of literature on psychological quality of life, a systematic review of perceived physical health in OCD is lacking. A quantitative summary might suggest that policy makers also focus the evaluation on perceived physical health and develop new strategies also aimed at this outcome. The current paper presents a protocol for the first systematic review and meta-analysis aimed at summarising perceived physical health in OCD by specifically examining perceived physical health status, bodily pain and role limitations due to physical problems in patients with OCD compared with controls. The review will also investigate potential demographic and clinical moderators of perceived physical health status (age, gender, OCD severity, publication date, methodological quality). Methods and analysis: A systematic review and meta-analysis will be conducted according to PRISMA guidelines. Studies will be included if using a clinical group with a current primary diagnosis of OCD established by international standardised criteria, if measuring perceived physical health status, and if using screened or community participants as controls. No publication date or language restriction will be applied. An online systematic search of electronic databases (Scopus, PubMed, PsycINFO, EMBASE, Cochrane Library), and examination of conference proceedings and theses/dissertations will be conducted by independent reviewers. Risk of bias will be assessed through the Newcastle-Ottawa Scale. Ethics and dissemination: The current review does not require ethics approval. The results will be disseminated through publications in peer-reviewed journals. PROSPERO registration number: 2018 CRD42018106194.